2021
DOI: 10.1038/s41576-021-00363-7
|View full text |Cite
|
Sign up to set email alerts
|

Mining genomes to illuminate the specialized chemistry of life

Abstract: This article is made publicly available in the institutional repository of Wageningen University and Research, under the terms of article 25fa of the Dutch Copyright Act, also known as the Amendment Taverne. This has been done with explicit consent by the author.Article 25fa states that the author of a short scientific work funded either wholly or partially by Dutch public funds is entitled to make that work publicly available for no consideration following a reasonable period of time after the work was first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
117
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 166 publications
(118 citation statements)
references
References 245 publications
0
117
0
1
Order By: Relevance
“…In the past decades, thousands of bacterial genomes have been deposited in public database, however, most of them are emphasized for functional genomics study [42] . To expand the usage of bacterial genomes, we have developed a platform ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In the past decades, thousands of bacterial genomes have been deposited in public database, however, most of them are emphasized for functional genomics study [42] . To expand the usage of bacterial genomes, we have developed a platform ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…196 Sequencing a single bacterial genome costs just a fraction of that. Because of this unprecedented access to genomic data, genome mining has become integral to the field of natural products 12 and birthed a renaissance in natural product discovery. 197 …”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, genomics-based approaches to NP discovery [11][12][13] have revealed that an untapped source of biosynthetic potential lies hidden in the genomes, which displays much greater diversity than the compounds in use so far 5,14,15 . These findings were possible due to the discovery that bacterial genes encoding the biosynthesis of secondary metabolites are usually located in close proximity to each other, forming recognizable Biosynthetic Gene Clusters (BGCs).…”
Section: Introductionmentioning
confidence: 99%